Identification of the Distribution and Volume of Iron Sand in the Gura Beach Area Using the Wenner-Schlumberger Configuration Geoelectric Method - Yumarti G B Tjinta; Bayu Achil Sadjab; Kurnia Kurnia; Harsen Berg Janis; Masitah Yusniar; Oktosea Buka; Steven Iwamoni; Adrian Rahmat Nur (International Journal of Hydrological and Environmental for Sustainability, 2023)
The Naniura NRD300 HF tool has been used in research using the Wenner-Schlumberger configuration geoelectric method to determine the direction of iron sand distribution, the volume of iron sand, and the concentration of iron sand in the Gura beach area. The collected measurement results are then processed by the RES2DINV software into a 2 Dimension (2D) cross-section that shows the distribution values of the subsurface layer as shown by a color image. Once saved in (.xyz) format, the RES2DINV software results are processed in RockWork software to create pseudo-3D cross sections. The RES2DINV software's results show that line 1's resistivity value ranges from 39.6 to 1000 Î©m, whereas line 2's resistivity value ranges from 0.16 to 1.7 Î©m. These findings suggest that line 2 has a lower resistivity value than line 1 does. The volume of iron sand processed by RockWork software is 221,000 cubic meters for linek 2 and 273,000 cubic meters for line 1. The distribution of iron sand deposits in the study region is south to north, based on the volume of iron sand in line 1, which is bigger. A method used to determine the composition of the minerals present in a sample is called X-ray fluorescence (XRF). The results of analyzing the Fe content in line 2 are 55.01%, which is higher when compared to the Fe content in line 1, which is 40.5%.